The Association Between Life’s Essential 8 and Psoriasis in American Adults: A Cross-Sectional NHANES Study - Zhang W; Yuan Z; Wang Y; Jin Z; Luo Z; Wang X (Clinical, Cosmetic and Investigational Dermatology)
Weiqing Zhang,1,* Zengze Yuan,1,* Yihan Wang,1 Zhaokai Jin,2 Ziyue Luo,1 Xinchang Wang1 1The Second Affiliated Hospital of Zhejiang Chinese Medical University (Xinhua Hospital of Zhejiang Province), Hangzhou, Zhejiang, People’s Republic of China; 2The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xinchang Wang, Email ossani@126.comPurpose: Life’s Essentials 8 (LE8) is a new indicator developed by the American Heart Association to assess cardiovascular health, including diet, physical activity, nicotine exposure, sleep health, body mass index, blood lipids, blood glucose and blood pressure. And more and more studies have shown that this index can evaluate other diseases, such as chronic kidney disease, abdominal aortic calcification and so on. However, there is no relevant study to evaluate the association between LE8 and psoriasis. The purpose of this study was to investigate the relationship between LE8 and the prevalence of psoriasis in American adults.Patients and Methods: The data are from the National Health and Nutrition Examination Survey (NHANES) of the United States from 2003 to 2006, 2009 to 2014. Psoriasis was the dependent variable. LE8 is an independent variable and is divided into three levels: high, medium and low. Multivariate logistic regression model was used to explore the relationship between LE8 and psoriasis.Results: A total of 13430 people were included in this study, including 391 patients with psoriasis and 13039 patients without psoriasis. The prevalence of psoriasis was 2.91%. In the fully adjusted logistic regression model, LE8 score was negatively correlated with psoriasis (OR=0.99; 95% CI, 0.98– 0.99, P=0.0003). And this result still exists when LE8 is divided into high, medium and low groups. Compared with the low LE8 group, the high LE8 group had a 61% lower risk of psoriasis (OR=0.39; 95% CI, 0.26– 0.57, p < 0.0001).Conclusion: This cross-sectional study suggested that LE8 score was negatively correlated with psoriasis risk.Keywords: Life’s Essentials 8, NHANES, Cross-sectional study, Psoriasis